PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP TINGKAT RENTABILITAS MODAL SENDIRI PADA KOPERASI WANITA TIMAH â€œKARYA RINIâ€ PANGKALPINANG - Setiawati, Epa; Makrus, Mohamad; Deseria, Rita (ECONOS Jurnal Ekonomi dan Sosial, 2019)
This study aims to determine the profitability value of the amount of own capital to the amount of profit to be obtained, assuming that the greater the profit, the greater the value of profitability.  The object in this study was 36 "KaryaRini" Tin Women Cooperative Pangkalpinang.  Data collection techniques in this study were documentation techniques, using descriptive analysis with multiple linear regression models.  The results showed that self-capital and loan capital had an effect on profitability.  Capital itself had a positive effect and loan capital had a negative effect on profitability.